1987
DOI: 10.1104/pp.84.1.82
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Phosphoenolpyruvate Carboxylase Activity in Maize Leaves

Abstract: The aim of this work was to investigate how light regulates the activity of phosphoenolpyruvate carboxylase in vivo in C4 plants. The properties of phosphoenolpyruvate carboxylase were investigated in extracts which were rapidly prepared (in less than 30 seconds) from darkened and illuminated leaves of Zea mays. Illumination resulted in a significant decrease in the So.5(phosphoenolpyruvate) but there was no change in V,,,. The form of the enzyme from illuminated leaves was less sensitive to malate inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
66
1
4

Year Published

1987
1987
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 21 publications
3
66
1
4
Order By: Relevance
“…Further studies demonstrated a transient peak of PEP during the initial phase of induction in maize leaves, suggesting that there is also a limitation on PEP carboxylase during this period (9,28). This phenomenon coincides well with recent findings of a light modulation of PEP carboxylase (5,13). Modulation of PEP carboxylase by light has been initially reported in several C4 species with a 2-to 3-fold increase following a dark to light transition (17,18,25).…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Further studies demonstrated a transient peak of PEP during the initial phase of induction in maize leaves, suggesting that there is also a limitation on PEP carboxylase during this period (9,28). This phenomenon coincides well with recent findings of a light modulation of PEP carboxylase (5,13). Modulation of PEP carboxylase by light has been initially reported in several C4 species with a 2-to 3-fold increase following a dark to light transition (17,18,25).…”
supporting
confidence: 71%
“…Modulation of PEP carboxylase by light has been initially reported in several C4 species with a 2-to 3-fold increase following a dark to light transition (17,18,25). However, recent reports revealed that there were up to 30-fold differences in PEP carboxylase activity during dark to light transitions in maize when assayed in simulated conditions of dark or light or in the presence of effectors (5,13). Studies of metabolite levels during induction in maize leaves (9,20,28) provided a basis for in vitro simulation ofconditions in vivo.…”
mentioning
confidence: 96%
“…3C). Both malate and PPrv, when evaluated at physiological levels [4], decreased phosphorylation of the carboxylase, possibly by their known interaction with the target protein.…”
Section: Functional and Regulatory Properties Of C Kinasementioning
confidence: 99%
“…Several primary metabolites have been reported to influence the activity of PPC in vitro, including malate (allosteric inhibitor) and glucose 6-phosphate (allosteric activator) (Doncaster and Leegood, 1987;Vidal and Chollet, 1997). For a CAM leaf, as the dark period progresses, the vacuolar storage capacity for malic acid reaches its limit, and malate begins to accumulate in the cytosol where it feeds back to inhibit PPC activity.…”
Section: Introductionmentioning
confidence: 99%